Sex Cord-Gonadal Stromal Tumor of the Rete Testis - Kamran P. Sajadi; Rory R. Dalton; James A. Brown (Advances in Urology)
A 34-year-old tetraplegic patient with suppurative epididymitis was found on follow-up examination and ultrasonography to have a testicular mass. The radical orchiectomy specimen contained an undifferentiated spindled sex cord-stromal tumor arising in the rete testis. Testicular sex cord-stromal tumors are far less common than germ cell neoplasms and are usually benign. The close relationship between sex cords and ductules of the rete testis during development provides the opportunity for these uncommon tumors to arise anatomically within the rete tesis. This undifferentiated sex cord-stromal tumor, occurring in a previously unreported location, is an example of an unusual lesion mimicking an intratesticular malignant neoplasm.